On the issue of the role of perception in the processes of secondary nomination - I N Ivashkevich (Polylinguality and Transcultural Practices, 2011)
The article is devoted to the study of the role of perception in the formation of new concepts in modern English in the processes of secondary nomination which are closely connected with dynamics of cognitive mechanisms of knowledge and human thought.